Adult exposure influences offspring response to ocean acidification in oysters - Parker, L M; Ross, P M; O'Connor, W A; Borysko, L; Raftos, D A; Pörtner, H O (Global Change Biology, 2012)
It is essential to predict the impact of elevated Pco 2 on marine organisms and habitats to anticipate the severity and consequences of future ocean chemistry change. Despite the importance of carry-over effects in the evolutionary history of marine organisms, few studies have considered links between life-history stages when determining how marine organisms will respond to elevated Pco 2, and none have considered the link between adults and their offspring. Herein, we exposed adults of wild and selectively bred Sydney rock oysters, Saccostrea glomerata to elevated Pco 2 during reproductive conditioning and measured the development, growth and survival response of their larvae. We found that elevated Pco 2 had a negative impact on larvae of S. glomerata causing a reduction in growth, rate of development and survival. Exposing adults to elevated Pco 2 during reproductive conditioning, however, had positive carry-over effects on larvae. Larvae spawned from adults exposed to elevated Pco 2 were larger and developed faster, but displayed similar survival compared with larvae spawned from adults exposed to ambient Pco 2. Furthermore, selectively bred larvae of S. glomerata were more resilient to elevated Pco 2 than wild larvae. Measurement of the standard metabolic rate (SMR) of adult S. glomerata showed that at ambient Pco 2, SMR is increased in selectively bred compared with wild oysters and is further increased during exposure to elevated Pco 2. This study suggests that sensitive marine organisms may have the capacity to acclimate or adapt to elevated Pco 2 over the next century and a change in energy turnover indicated by SMR may be a key process involved. © 2011 Blackwell Publishing Ltd.